2009
DOI: 10.1515/cclm.2010.043
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 27 is over-expressed in tumor tissues and increased in sera of patients with gastric adenocarcinoma

Abstract: Background: In a previous study, we found that heat shock protein 27 (HSP27) was over-expressed in gastric adenocarcinoma (GA) tissue. In this study, our goal was to further verify the expression profile of HSP27 in patients with GA. Methods: Western blot and immunohistochemistry were employed to determine HSP27 expression in 50 paired tumor and adjacent normal tissue. ELISA was used to quantify serum HSP27 concentrations in the same 50 GA patients and 50 healthy individuals. Results: Compared to adjacent norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 38 publications
1
41
0
1
Order By: Relevance
“…Circulating sHsp27 levels were significantly higher in patients with HCC than in healthy control subjects. Previous studies have reported elevated sHsp27 levels in patients with breast cancer (Fanelli et al 1998;Banerjee et al 2011), non-small cell lung cancer (Zimmermann et al 2012) and both pancreatic and gastric adenocarcinoma (Melle et al 2007;Huang et al 2010); however, this is the first report of a rise in circulating sHsp27 levels in patients with HCC.…”
Section: Discussionmentioning
confidence: 56%
“…Circulating sHsp27 levels were significantly higher in patients with HCC than in healthy control subjects. Previous studies have reported elevated sHsp27 levels in patients with breast cancer (Fanelli et al 1998;Banerjee et al 2011), non-small cell lung cancer (Zimmermann et al 2012) and both pancreatic and gastric adenocarcinoma (Melle et al 2007;Huang et al 2010); however, this is the first report of a rise in circulating sHsp27 levels in patients with HCC.…”
Section: Discussionmentioning
confidence: 56%
“…The role of miR-145 in the maintenance of high level of Hsp-27 was not through direct gene targeting but stabilization of Hsp-27. Although the role and clinical outcome of Hsp-27 in primary tumors has been well studied and documented [33], its function in metastasis invasion is still unclear. Further investigations to identify the mechanism of Hsp-27 involved in CRC metastasis will further enrich our understanding on the up-regulation of miR-145 in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…HSPB1 is another chaperone secreted by cells in a non-classical pathway [94] associated to exosomes [93]. In vivo, serum HSPB1 was observed increased in pancreatic carcinoma [95], hepatocellular carcinoma [96], breast cancer [97] and gastric adenocarcinoma patients [98]. …”
Section: Unconventional Mechanisms Of Hsp Secretionmentioning
confidence: 99%